Systematic placement of the enigmatic genus Timesius Simon, 1879 (Opiliones, Laniatores, Nomoclastidae), with description of a new species from the Colombian Andes - Damron, Brittany; Moreno-González, Jairo A.; Pinto-Da-Rocha, Ricardo (Zootaxa, 2025)
The enigmatic monotypic genus Timesius Simon, 1879, hitherto assigned to Stygnidae Simon, 1879, is redescribed and its phylogenetic position inferred upon morphological and molecular evidence, resulting in its reallocation to the family Nomoclastidae Roewer, 1943. The type material of Timesius vesicularis (Gervais, 1844), long presumed lost, was rediscovered, and is hereby redescribed and illustrated. Also, a new species, Timesius paramuno sp. nov., is described based on specimens collected in the Páramo ecosystem in the Central Cordillera, Colombia. Timesius vesicularis can be readily distinguished by having two long spines on area III of the dorsal scutum (two short tubercles in T. paramuno sp. nov.) and small whitish-yellow granules on the ocularium and dorsal scutum (vestigial whitish-yellow granules in T. paramuno sp. nov.).